Stress-induced domain wall motion in FeCo-based magnetic microwires for realization of energy harvesting - Bhatti, Sabpreet (2020)
Energy harvesting is getting significant interest due to the emergence of Internet of Things (IoT). As IoT devices are required to generate power on their own, several researchers are studying ferroelectric materials for voltage generation. However, ferroelectric materials suffer from high resistance at low frequencies, which reduces the output power. Domain wall propagation in ferromagnetic materials, as induced by stress and a pickup voltage using coils, is investigated as an alternate form of energy harvesting. Such studies, which are reported in multiferroic structures, feature a voltage applied to induce the stress, which defeats the purpose of self-power generation. Here, power generation from mechanical vibrations in purely ferromagnetic structures is shown. These results are achieved by showing that the domain walls can be moved entirely by stress in a trilayer stack of ferromagnetic microwires. The use of flexible substrates with low Young's modulus and a trilayer magnetic stack enables the achievement of significant magnetization rotation or domain wall motion even from ambient vibrations. Here, the rotation of magnetization or domain wall motion is exploited to induce voltages in the pickup coils. The results shown here provide an alternative way to power IoT devices.